Prácticas agronómicas para la conservación de los suelos agrícolas en PACASMAYO - LA LIBERTAD - Rodríguez Llicán, Rosa María (2012)
This work was conducted during July 2012 to December 2012, in the province of Pacasmayo, La Libertad Region. The primary objective was to determine the most appropriate agronomic practices in agricultural soil conservation in Pacasmayo. Within the model of conventional agriculture, soil resources has been considered simply as an inert carrier - source of nutrients - for plant development, which could be applied agrochemicals without any environmental consideration, did not understand that this resource known to our ancestors as "Pachamama" is alive and dynamics is closely related to the cycles of nature. A soil suitable for agriculture are the scarcest resource of the country (7% of the country) and also is the most threatened by degradation processes, especially in the coastal salinization, erosion in the mountains and gradual loss of fertility in the Amazon. A total of 8 million hectares are classified as severely eroded and 31 million hectares are moderately eroded. It is estimated that at least 40% of the agricultural soils of Costa processes are affected by salinity and poor drainage. Furthermore, the annual flood of the rivers in the summer and when the phenomenon of El Niño and lack of river defenses are lost large areas of scarce agricultural land. Cartographic material was used in the area: The geographic and cartographic map, in order to gather the information needed to make this work which was finally determined that in the province of Pacasmayo to preserve better agricultural soils should prioritize agronomic practices such as farm irrigation management, crop rotation, cover crops and green manures, crop tillage organic and chemical amendments, windbreaks and reforestation in certain sectors, as the soil and climate and agricultural suitability of the study area.